COVID-19 infection and its impact on case fatality in patients with pulmonary embolism - Hobohm, Lukas; Sagoschen, Ingo; Barco, Stefano; Farmakis, Ioannis T.; Fedeli, Ugo; Koelmel, Sebastian; Gori, Tommaso; Espinola-Klein, Christine; Münzel, Thomas; Konstantinides, Stavros; Keller, Karsten (The European respiratory journal, 2023)
Although a high prevalence of pulmonary embolism (PE) has been reported in association with coronavirus disease 2019 (COVID-19) in critically ill patients, nationwide data on the outcome of hospitalised patients with COVID-19 and PE are still limited. Thus, we investigated seasonal trends and predictors of in-hospital death in patients with COVID-19 and PE in Germany.
Gesehen am 22.03.2023